A review of perioperative treatment strategies with immunotherapy and tyrosine kinase inhibitors in resectable and stage IIIA-N2 non-small cell lung cancer - Hopson, Madeleine B.; Rashdan, Sawsan (Frontiers in Oncology, 2024)
Stage IIIA-N2 non-small cell lung cancer (NSCLC) is a heterogeneous group with different potential therapeutic approaches. Treatment is typically multimodal with either surgical resection after neoadjuvant chemotherapy and/or radiation or concurrent chemotherapy and radiation if unresectable. Despite the multimodal treatment and early stage, cure rates have traditionally been low. The introduction of immunotherapy changed the treatment landscape for NSCLC in all stages, and the introduction of immunotherapy in early-stage lung cancer has improved event free survival and overall survival. Tyrosine Kinase inhibitors (TKIs) have also improved outcomes in early-stage mutation-driven NSCLC. Optimal treatment choice and sequence is increasingly becoming based upon personalized factors including clinical characteristics, comorbidities, programmed death-ligand 1 (PD-L1) score, and the presence of targetable mutations. Despite encouraging data from multiple trials, the optimal multimodal sequence of stage IIIA-N2 NSCLC treatment remains unresolved and warrants further investigation. This review article summarizes recent major clinical trials of neoadjuvant and adjuvant treatment including stage IIIA-N2 NSCLC with a focus on immunotherapy and TKIs.